2013
DOI: 10.1177/0885066613492645
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Associated Graft Versus Host Disease in the Immunocompetent Patient

Abstract: Transfusion associated-graft versus host disease (TA-GVHD) is a rare complication of blood transfusion. It carries a very high mortality rate. Although the phenomenon has been well described in immunocompromised patients, this review focuses on the immunocompetent host. Cases of TA-GVHD continue to be reported following a variety of surgical procedures, especially cardiac procedures requiring cardiopulmonary bypass. Additional risk factors for TA-GVHD include blood component transfusion in populations with lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 61 publications
2
17
0
3
Order By: Relevance
“…Prevention of TA‐GVHD is accomplished by using gamma‐irradiated blood components for patients at risk; however, identifying such patients is challenging. TA‐GVHD was first recognized in patients with varying degrees of immunosuppression, although early instances from Japan and later instances of family donors around the world highlighted that immunocompetent patients may still be susceptible to the disease when their genetic similarity with the donor T cells makes their immune system unable to defend against donor cell attack . In addition, immune suppression may be difficult to predict, as it is affected by factors such as genetic makeup, age, etc., and can be temporarily induced by disease and trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of TA‐GVHD is accomplished by using gamma‐irradiated blood components for patients at risk; however, identifying such patients is challenging. TA‐GVHD was first recognized in patients with varying degrees of immunosuppression, although early instances from Japan and later instances of family donors around the world highlighted that immunocompetent patients may still be susceptible to the disease when their genetic similarity with the donor T cells makes their immune system unable to defend against donor cell attack . In addition, immune suppression may be difficult to predict, as it is affected by factors such as genetic makeup, age, etc., and can be temporarily induced by disease and trauma.…”
mentioning
confidence: 99%
“…TA-GVHD was first recognized in patients with varying degrees of immunosuppression, although early instances from Japan 5 and later instances of family donors around the world 6,7 highlighted that immunocompetent patients may still be susceptible to the disease when their genetic similarity with the donor T cells makes their immune system unable to defend against donor cell attack. 8 In addition, immune suppression may be difficult to predict, as it is affected by factors such as genetic makeup, age, etc., and can be temporarily induced by disease and trauma. A recent review of the literature showed that approximately 60% of TA-GVHD cases followed transfusion of nonirradiated blood components to recipients not identified as being at risk, indicating that treatment of all components may be a better strategy.…”
mentioning
confidence: 99%
“…The risk factors of this disease include the number and immunoreactivity of contaminating lymphocytes in transfusion components. The dominant mechanism of TA-GVHD in immunocompetent and compromised hosts is exposure to viable donor lymphocytes that are responsive against recipients but are not recognized as foreign substances (3,15) . Similar to GVHD, TA-GVHD requires an immunoactive component, difference in MHC between a donor and a recipient, and susceptibility of a patient's immune system to the engraftment of donor lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive patients who receive blood transfusion containing immuneactive lymphocytes are prone to serious clinical syndromes (2) . With extensive applications of immunosuppressive nucleotide analogs, such as fludarabine, the incidence of TA-GVHD increases annually (3) . TA-GVHD usually occurs in immunosuppressive and immunodeficient patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation